Cytokine status indicators in children with acute respiratory viral infections after treatment with intranasal interferon-based medicine - O. I. Afanasyeva; E. G. Golovacheva; L. V. Osidak; V. S. Timonina; V. V. Gonchar; E. V. Obraztsova; E. A. Dondurey; E. S. Goncharova; A. S. Simbirtsev; D. A. Lioznov (Детские инфекции (Москва))
Objective: to study the dynamics of local and systemic cytokine production in children with different clinical forms of acute respiratory viral infections (ARVI), including COVID-19, and to assess the effectiveness of local interferon-based therapy.Patients and methods: The study included 180 patients aged from 1 month to 17 years with сonfirmed acute respiratory viral infections (ARVI), including COVID-19. Patients were divided into 2 groups (main and control) of 90 people each. In the main group patients received the intranasal interferon-based medicine Grippferon® in addition to the basic therapy, the control group patients received only basic therapy. The cytokine status was assessed by the content of IFN-α and -γ, IL-1β, IL-8, IL-4, IL-10, IL-17 in blood serum and in nasopharyngeal secretions by enzyme immunoassay kits ("Cytokine", St. Petersburg).Results: Statistically significant differences were revealed in the systemic and local content of individual cytokines in ARVI of different etiologies, depending on the level of damage to the respiratory tract. The use of the interferon-based medicine Grippferon® for intranasal use in children in the early stages of ARVI, including COVID-19, helps to decrease the high content of cytokines IL-1β and IL-8 in the nasopharynx by reducing the viral load. As a result, the duration of catarrhal disease symptoms and intoxication was also significantly reduced as well as the pathogen elimination time.